Etika Komunikasi Dalam Al-Qur’an - Ismail (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This research needs to be studied to find out about the ethics of communication within the Qur'an. Based on the concept in the Qur'an, that is, humans are religious beings and also social beings, namely creatures that always live in a society and always need the participation of other parties. That is, living in a society is something that grows in accordance with human nature and needs. In the Al-Qur'an many provide direction or positive value values that must be developed, as well as negative values that should be avoided. Because in al Alqur'an / 49: 13 it shows that mutual acquaintance which is meant does not distinguish ethnicity, race, language, culture, even ideology. But in reality humans as ethical value makers (homo ethicuc) often have cultural and ethical differences that each adheres to. So that in this case there needs to be ethics in the communication process so that the communication will be established to be good (communicative), thus the relationship will be harmoniously established if between communicators and communicants grow mutual pleasure. Joy will arise if both respect and mutual respect will be born if both of them understand each other about one's characteristics and ethics that are believed by each. To obtain representative data in this discussion, the library research method (library reseach) is used by searching, collecting, reading, and analyzing books, which has relevance to research problems. Then processed according to the ability of the author. The research approach in this paper is content analysis. The method of discussing the interpretation in this writing is the maudhu method, which is a method of interpretation used by the interpreters in explaining the verses of the Qur'an as stated in the Mushaf. It starts with mentioning the verse to be interpreted. So here the author uses the theory of several interpretations of the Qur'an as the basic foundation for translating the verse, the author uses such as Tafsir al-Misbah, Tafsir al-Maraghi, Tafsir Ibn Kathir and Tafsir al-Azhar. After the author obtains the relevant references then the data is compiled, analyzed, so as to obtain conclusions.